A SYSTEM OF INDICATORS REPRESENTING THE EFFECTIVE USE OF FIXED ASSETS - Kurbanbaeva Iroda; Jengisbaev Musa (World Scientific Research Journal, 2025)
Annotation: Analyzing company’s system of indicators, this article discusses their reflection for the effective use of fixed assets. The effective use of fixed assets is crucial for advancing organizational performance and assuring long-term sustainability. A system of indicators representing the effective use of fixed assets provides a comprehensive access to measure, monitor, and improve asset utilization within an enterprise. This system typically comprises key performance indicators (KPIs) such as asset turnover ratio, return on assets (ROA), depreciation rates, and maintenance costs, all of which shed light on the efficiency and productivity of capital investments. By analyzing these indicators, businesses can identify underperforming assets, reduce operational costs, and enhance decision-making related to asset acquisition, maintenance, and disposal. This paper explores the importance of these indicators, highlights methodologies for their implementation, and discusses their role in achieving optimal fixed asset management. Additionally, it examines how these metrics can aid in strategic planning, financial forecasting, and operational improvements, thereby driving both short-term gains and long-term value creation.